Scapular kinematics during scaption in competitive swimmers. Issue 5 (28th May 2018) - Blache, Y.; Gillet, B.; Selin, J.; Sevrez, V.; Rogowski, I.
Abstract: This study aimed (1) to describe and compare scapular kinematics between three groups of swimmers of different levels and a group of non-swimmers, and (2) to assess whether swimming practice alters the asymmetries in scapular kinematics between the dominant and non-dominant sides, both during unilateral arm raising and lowering in the scapular plane. Scapular kinematics were assessed bilaterally during arm raising and lowering in the scapular plane using an electromagnetic system in 42 healthy males, which were split into four groups: control ( n = 11), adolescent elite swimmers ( n = 11), adult elite swimmers ( n = 10), and club-level adult swimmers ( n = 10). One-Way ANOVA SPM(t) on two repeated measures showed that the three groups of swimmers had more protracted shoulder between 30° and 90° of arm raising and lowering ( p < .001). The three groups of swimmers presented no bilateral difference in scapular upward rotation, while the dominant scapula was more upwardly rotated than the non-dominant one between 74° and 104° of arm elevation in the control group ( p < .001). The scapula of adult elite swimmers was more internally rotated between 67° and 116° of humeral elevation during arm raising, and between 81° and 54° during arm lowering in comparison to the other swimming and control groups ( p ≤ .02), who presented similar scapular positioning in internal rotation. In conclusion, the findings of the study pointed out that swimming practice generated protracted shoulders and removed bilateral differences in scapular upward rotation during scaption, while accumulation of swimming practice at elite level enlarged scapular internal rotation.